2008
DOI: 10.1099/mic.0.2007/013144-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of unstable Gfp variants to the kinetic study of Legionella pneumophila icm gene expression during infection

Abstract: An unstable type of green fluorescent protein (Gfp) tagged with a C-terminal extension, which is a target for tail-specific protease, was used as a reporter gene in Legionella pneumophila. To analyse Gfp expression in legionellae, transcriptional fusions of unstable gfp with the Legionella-specific icm (intracellular multiplication) promoters (P icmS , P icmT and P icmQ ) were constructed. Infection studies using J774.1 macrophages as the host, and L. pneumophila strains carrying P icmS -gfp, P icmT -gfp and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…mCherry expression was improved using the T7 RBS amplified from pNT28 using the primers oNP45 forward/reverse, generating the plasmid pSN2. To increase GFPsfm2-LAA degradation rate 74 , the sequence encoding the peptide tag AANDENYAAAV at the carboxyl terminus was generated by site-directed mutagenesis of pSN2 using the primers oNP28 forward/reverse (QuikChange II site-directed mutagenesis; Agilent) yielding the plasmid pSN5. A hairpin transcriptional terminator followed by a multiple cloning site was synthesized and inserted upstream the gene encoding gfpsfm2-aav , yielding the plasmid pSN6.…”
Section: Methodsmentioning
confidence: 99%
“…mCherry expression was improved using the T7 RBS amplified from pNT28 using the primers oNP45 forward/reverse, generating the plasmid pSN2. To increase GFPsfm2-LAA degradation rate 74 , the sequence encoding the peptide tag AANDENYAAAV at the carboxyl terminus was generated by site-directed mutagenesis of pSN2 using the primers oNP28 forward/reverse (QuikChange II site-directed mutagenesis; Agilent) yielding the plasmid pSN5. A hairpin transcriptional terminator followed by a multiple cloning site was synthesized and inserted upstream the gene encoding gfpsfm2-aav , yielding the plasmid pSN6.…”
Section: Methodsmentioning
confidence: 99%
“…Several variants of GFP have been generated that, in theory, could reduce the accumulation of detectable fluorescence in the vacuole. For example, protease‐sensitive variants, in which cleavage sites have been introduced into the sequence of GFP, are degraded upon delivery to sites of protease activity (3–5); however, their usefulness might be limited by the efficiency of cleavage. Instead, pH‐sensitive GFP variants, known as pHluorins, display changes in excitation and/or emission properties depending on the pH of their local environment (6).…”
mentioning
confidence: 99%
“…26,27) However, our results were in line with Barysheva et al and Katagiri et al showed that the total number of bacteria increased over time in murine J774.1A and Raw264.7 cells. 25,28) The reasons for the deviation are not very clear now. Among the non-phagocytic cell lines, MCF-7 and Beas-2B cells were better hosts for up to 24 h post-infection, whereas 16HBE was a proper host between 48 and 72 h post-infection.…”
Section: Discussionmentioning
confidence: 99%